Multimedia novels for internet generation (Net-Gen) readers in the cyberspace / Rosnidar Ain - Ain, Rosnidar (Institute of Graduate Studies, UiTM, 2016)
In the midst of rapid technological advance, a new era in literature writing has emerged. Wider network of Internet has given the opportunities to authors to become more prolific and creative in producing their work. In the virtual space, the number of authors grows and each one of them strives to grab the readers’ attention. Websites and social networking sites become the medium for authors to harness their creative mind through their writings. For writers who has envisioned becoming authors or writers who fail to establish themselves in the mainstream media, the Internet is perceived as a medium that is very easy for them to write. Nevertheless, with the impact of technological advances that covers almost all aspects of the public’s life, literary work is seen as not too distant from the conventional literature. The type of written material still resembles the printed ones. In fact, the use of multimedia is not fully utilized to produce literary work, which is different from the conventional literature materials. This study aims to analyze the novel as a genre in the Internet realm for the Internet generation (Net-Gen) through the utilization of multimedia in Malay literature…